Negative consequences and international migration of women in sri lanka - Jayathunga, N.S. (University of Jaffna, 2012)
Sri Lanka promoted migration after 1977 with the introduction of the open economic policies for the country and it affected to make widen the international relationship among nations. With the changing pattern of international relationships the rural social structure was also highly affected. The main objective of this study is to discuss the negative consequences which arise through the international migration of women in Sri Lankan context and how it was influenced to the family and children. Identifying the main reasons for the migration, the views of the husband on the migrated wife, the nature of the problem faced by the husband, the responses of the children on the migration of the mothers, views of the achievements of the expected goal through migration are the other specific objectives of this study. The purposive sampling was used by the study because the international migration is not a common for all households of the society. Sample was taken from Wariyapola DS division in Kurunagala district, which records high international migration rates in rural sectors. 50 households were selected including 38 cases from the women returned back after the migration and 12 cases from the family members who have migrated women at the moment. The questionnaire, interview, case studies and observation were used for the data collection. To get rid of economic problems, to build a new house, to buy a land, to save money, to solve the problems of the children and to achieve the economic status of the others, to get rid of economical problems including indebtedness, inability to find foods, insufficient income of the husband, the expenditure of the children’s education, lack of the household commodities and safety purpose are the major cause of the migration identified through this study. Alcohol addiction, sexual problems and mental depression are the leading problems faced by husbands. The main problems faced by the children due to mother’s migration are isolation, neglecting education, sexual harassment and loitering. Some possible policy implications were suggested as final contribution of this micro level study to address this social problem in Sri Lanka in a sociological aspect.
Keywords: Migration; Women; Family; Causes; Role conflict